Web‐Based Self‐Help for Preventing Mental Health Problems in Universities: Comparing Acceptance and Commitment Training to Mental Health Education. Issue 3 (19th January 2016) - Levin, Michael E.; Hayes, Steven C.; Pistorello, Jacqueline; Seeley, John R.
Abstract : Objective: This study sought to test the feasibility of a web‐based Acceptance and Commitment Training (ACT) prototype prevention program called ACT on College Life (ACT‐CL). Method: A sample of 234 university students was randomized to either the ACT‐CL website or a mental health education (MHE) website. Results: Findings indicated a lower level of user engagement and satisfaction ratings with the prototype of ACT‐CL than the MHE website. There were no significant differences between conditions on outcome measures at post or follow‐up. However, statistical trends suggested the MHE condition actually led to greater remission of severe symptoms than the ACT‐CL condition among those with severe symptoms at baseline. There were no differences between conditions on ACT process of change measures. Changes in psychological flexibility were predictive of changes in mental health across conditions, but relations dissipated over time. Furthermore, greater engagement in some components of ACT‐CL predicted improvements in psychological flexibility, though not on mental health outcomes. Conclusions: The effects of the ACT‐CL program on mental health outcomes and ACT process measures were largely equivalent to those of an education website, although there was a lower level of program engagement with ACT‐CL. Findings are discussed in the context of feasibility issues and lessons learned for program revisions.